Entre o dito e o não dito : os militares “heróis” e “comuns” da Guerra de Canudos - Morato, André Cavalcante (2022)
The present work aims to understand the military of the War of Canudos from the representations of the officers as "heroes", as well as to understand who the "common" were. At first, let's understand the "said" about the War and the military. The intention is to apprehend, from the reading of the Rio de Janeiro newspaper O Paiz, how the fight was reported in the press and how the officers were demonstrated as “heroes”. In the second part, we will understand the importance of the Army for the construction of representations of these subjects. From the idea of what was “remembered”, we will appreciate how a tribute to General Arthur Oscar was conceived with the aim of heroizing him, as well as highlighting places built to perpetuate the memory of some officers. In the last part of the work, space will be given to the “unspoken”, looking at the anonymous who did not have their names highlighted and were not honored. We will observe who these soldiers were, taking a look at their claims, memories and implications for themselves and their families. The research will make use of conceptual references such as memory, representations and power, respectively by the authors Jacques Le Goff, Roger Chartier and Pierre Bourdieu.